Factors affecting adoption of Agroforestry by women and youths in Mt. Elgon Region, Uganda - Galabuzi, C.; Sekatuba, J.; Agaba, H.; Werikhe, G.; Sekitto, I.; Carsan, S.; Okia, C.A.; Muthuri, Catherine W. (2020)
With the majority of the world’s poor living and working in developing countries, investment in agroforestry will only make sense if it addresses challenges of specific farming contexts. Even though agroforestry is beneficial to stakeholders in several ways, it has received mixed reactions from farming communities in the developing countries. Accordingly, adoption of “new” technologies has not been as fast as desired (Mwase2015). In Uganda agroforestry is spearheaded by the women and youth because they comprise a critical labor force on farm. In the Mt.Elgon region, interest in agroforestry technologies is low and yet prevailing soil and water management challenges require robust mechanism to addresst hem. Amongst them, is the integration of specific trees/shrubs on farms. A survey was undertaken in this region to assess the factors affecting adoption of agroforestry amongst women and youths. The objectives were to i) assess the socio- economic characteristics of farmers, ii) assess the benefits from agroforestry technologies and iii) identify challenges, incentives and strategies towards adoption of agroforestry among the women and youths.